Struktur dan Fungsi Sosial Pantun Pernikahan di Pasaman Barat - Adilla Hawari; Muhammad Adek (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Minangkabau-language pantuns are rare to find in today's modern times. Therefore, preservation efforts are needed through cultural documentation and research on oral literature. This study aims to describe the structure and social functions of pantun in Minangkabau language. This research belongs to literary research, especially oral literature. The data of this study are the utterances of Minangkabau pantuns contained in Minangkabau cultural wedding ceremonies which were collected through structured interviews with pantuns’ speakers. The results of this study are: (1) the structure of the pantun in wedding ceremonies in West Pasaman Regency, divided into physical and mental structures and; (2) the social function of pantuns in Minangkabau weddings includes (a) a means of communication, (b) identity of the Minangkabau people, (c) decoration of the oral tradition of the Minangkabau people, (d) a means of preaching, (e) a means of educating.